THU0423 The relationship between clinical disease activity, symptom duration and ultrasonographic changes in gout. (15th June 2017) - Norkuviene, E; Petraitis, M; Apanaviciene, I; Virviciute, D; Baranauskaite, A
Abstract : Background: Ultrasonography (US) has recently been validated and used as an objective diagnostic tool for urate deposition also joint damage and was proposed as an outcome measure in gout [1–2]. Objectives: Our aim was to investigate the relationship between clinical gout activity and load of US changes. Methods: Sixty monosodium-urate-crystal-confirmed gout patients (52 men) and 36 healthy normouricemic controls were prospectively included in one centre. The relationship between clinical symptoms and US gout-related changes investigating 36 joints and 4 tendons (m. triceps and patellar) was evaluated using Spearman's correlation. Results: The total number of intraarticular T, periarticular T, total T, total DC, and total E found per patient on ultrasound ranged from 0–26, 0–4, 0–30, 0–29, and 0–18, accordingly.The number of acute attacks per year/per life had a significant positive correlation with the total number of intraarticular T (rs=0.518/0.652; p<0.0001), total number of intraarticular and periarticular T (rs=0.552/0.699; p<0.0001), the total number of DC (rs=0.374/0.551; p<0.01), the total number of erosions (rs=0.374/0.542; p<0.01), and the total tophus area (rs=0.420/0.549; p<0.01) measured on US per patient. Strong, positive correlation was observed between the number of subcutaneous tophi and total US tophus area (rs=0.628), total number of DC (rs=0.612) and erosions (rs=0.526), found per patient on US, all p<0.0001. Disease duration significantly positively correlated with the load of US T, E and DC (p<0.0001) in the investigated sites. There was no correlation between CRP and US, also no correlation between the uric acid concentration and US changes: total number of T (rs=0.193, p=0.139), DC (rs=0.179, p=0.170) or E (rs=0.063, p=0.634) found per patient. The tophus area measured in two first metatarsophalangeal joints (MTP) positively correlated with subcutaneous tophus count (rs=0, 404; p=0, 001), the US intraarticular T count (rs =0, 732; p<0, 0001) total US DC count (rs =0, 477; p<0, 0001) total intraarticular tophus area (rs =0, 829; p<0, 0001)and total tophus area other than first MTP joints (rs =0, 603; p<0.0001). Conclusions: Ultrasonographic gout -related changes strongly positively correlate between each other and with subjective also objective signs of disease activity, increasing with disease duration in gout. The size of tophi inside the first metatarsophalangeal joints could be representative of the total body urate load and could be chosen as an outcome measure for the longitudinal gout studies. References: Neogi T, Jansen TLTA, Dalbeth N, Fransen J, Schumacher HR, Berendsen D, et al. 2015 Gout classification criteria: an American College of Rheumatology/European League Against Rheumatism collaborative initiative. Ann Rheum Dis. 2015 Sep 9; 74(10):1789–98. Ottaviani S, Gill G, Aubrun A, Palazzo E, Meyer O, Dieudé P. Ultrasound in gout: a useful tool for following urate-lowering therapy. Jt Bone Spine 2015 Jan; 82(1):42–4. Disclosure of Interest: None declared